Microbiological evaluation in invisible aligner chemical cleaning methods against Candida albicans and Streptococcus mutans - Bonafé, Ana Carolina Ferreira [UNESP]; Oliveira, Daniela Fernandes Lobo Molica [UNESP]; Fernandes, Ellen Eduarda [UNESP]; Garcia, Maíra Terra [UNESP]; Dias, Isis Patrícia Soares Silva [UNESP]; Bressane, Adriano [UNESP]; de Oliveira, Wagner [UNESP]; de Mello Rode, Sigmar [UNESP] (Elsevier, 2023)
Introduction: This study aimed to assess the efficacy of chemical agents in removing Candida albicans and Streptococcus mutans biofilm from invisible aligners. Methods: The samples were made of EX30 Invisalign trays, biofilm was cultured by standardized suspensions of C. albicans ATCC strain and S. mutans clinical strain on the sample. The treatments used were 0.5% sodium hypochlorite (NaClO) (20 minutes), 1% NaClO (10 minutes), chlorhexidine (5 minutes), peroxide (15 minutes), and orthophosphoric acid (15 seconds). The control group received phosphate-buffered saline for 10 minutes. The colony-forming units per milliliter of each microorganism were determined by serial dilutions seeded in plates with selective culture mediums for each one. Data were analyzed by the Kruskal-Wallis and Conover-Iman tests at an α of 0.05. Results: For the C. albicans biofilm group, the control group had 9.7 Log10 of microorganism growth, and all treatment groups had statistically significant biofilm reduction, in which chlorhexidine presented the highest inhibition of 3 Log10, followed by alkaline peroxide and orthophosphoric acid both with 2.6 Log10, 1% NaClO (2.5 Log10), and 0.5% NaClO (2 Log10). As for S. mutans, the control group had 8.9 Log10 of growth, and a total microorganism inhibition was reached by chlorhexidine, 1% NaClO, and orthophosphoric acid, whereas alkaline peroxide inhibited growth to 7.9 Log10 and 0.5% NaClO 5.1 Log10. Conclusions: Within the limitations, chlorhexidine and orthophosphoric acid had greater efficacy in both biofilms. In addition, 1% NaClO and alkaline peroxide also had significant effects; therefore, their incorporation aligners disinfection protocols are valid.